1990
DOI: 10.1016/0142-9612(90)90105-y
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of porous acrylic cement in soft tissues: an animal and human biopsy histological study

Abstract: Long-term (8 and 24 month) reactions of the (hypo) dermis of the guinea pig to solid and porous (50 vol%) acrylic implants and four human biopsies from porous subcutaneous acrylic implants were studied light microscopically. The solid implants were encapsulated by dense connective tissue. Mobility was evidenced by the loss of 4 out of 36 after 2 yr and was considered the explanation for the occurrence of ectopic cartilage and mineralized material at some solid implants' surfaces after 2 yr. A dense capsule was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…In a long-term study in guinea pigs comparing porous and solid PMMA implanted in the hypodermis, van Mullem et al reported implant extrusion occurred in 4/36 solid implants and none of the porous implants. 26 Similar to the present study, the same study noted that foci of inflammatory cells were found more frequently around and within the porous PMMA implants (1:1 aqueous phase:polymer phase) than the solid implants. Clinically, the porous PMMA seems to have been used successfully with little note of complications, 66 and, although reports of long-term results are rarely found, the current study differs from those previously published as the intent is for the porous implants to only be used as temporary implants.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In a long-term study in guinea pigs comparing porous and solid PMMA implanted in the hypodermis, van Mullem et al reported implant extrusion occurred in 4/36 solid implants and none of the porous implants. 26 Similar to the present study, the same study noted that foci of inflammatory cells were found more frequently around and within the porous PMMA implants (1:1 aqueous phase:polymer phase) than the solid implants. Clinically, the porous PMMA seems to have been used successfully with little note of complications, 66 and, although reports of long-term results are rarely found, the current study differs from those previously published as the intent is for the porous implants to only be used as temporary implants.…”
Section: Discussionsupporting
confidence: 87%
“…Previously, a number of groups have explored different methods for making porous PMMA. [23][24][25][26][27][28] On the basis of this work, we hypothesized that porous PMMA implants with reproducibly tunable pore structure could be fabricated using a carboxymethylcellulose (CMC) hydrogel as an aqueous porogen. When tested in a clean/contaminated rabbit mandibular defect, we hypothesized that these implants would be able to maintain the defect space while promoting soft tissue coverage of the implant.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be molded intraoperatively to fill complex defects, making PMMA implants particularly suited for osseous space maintenance in oral and craniofacial reconstructions [9, 15-17]. While conventional PMMA cement has been previously used in space maintenance applications, problems with implant extrusion or wound dehiscence have been reported [10, 11, 18]. It has been demonstrated that the porous structure of an implant material plays an essential role in anchoring the material to the host by allowing for rapid ingrowth of fibrovascular and soft tissue into the pores to promote wound healing and the formation of a stable interface [10, 18-22].…”
Section: Introductionmentioning
confidence: 99%
“…This mobility is observed in the implants of solid bone cements rather than in porous bone cements. 23 The analysis of the explanted rods by optical microscopy revealed some changes with respect to preimplanted rods, showing a smooth texture where the irregularities or defects present in the initial surfaces have disappeared. This small erosion can be related to the inflammatory response, which takes place in the first 2 days after implantation.…”
Section: Discussionmentioning
confidence: 98%